2009
DOI: 10.1007/s00284-009-9485-9
|View full text |Cite
|
Sign up to set email alerts
|

Poly-β-Hydroxyalkanoate Exert a Protective Effect Against Carbon Starvation and Frozen Conditions in Sphingopyxis chilensis

Abstract: Several bacterial species have developed physiological response to avoid the cellular damage when are exposed to carbon starvation or frozen stress. For example survival to inanition has been related to endogenous substrates consumptions. The aim of this study was to evaluate if poly-beta-hydroxylkanoates (PHA) consumption enable Sphingopyxis chilensis S37 to survive under carbon starvation or frozen condition. Bacterial cells were grown in R(2)A broth for 48 h, and suspended in mineral saline solutions, witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Thus, it seems that intracellular reserves of PHB also play an important role in the freezing survival of bacteria, which is in agreement with the observations of other authors. Pavez et al identified PHA accumulation in the bacterium Sphingopyxis chilensis (isolated from an oligotrophic aquatic environment where the temperature oscillates around 0°C) as the most important feature protecting cells from freezing conditions [ 13 ]. Moreover, PHA-producing bacteria were isolated from Antarctic freshwater [ 14 ] and Antarctic soil [ 15 ] confirming PHA accumulation as an efficient adaptation strategy for avoiding damage produced by intracellular ice crystals, oxygen-reactive species, and severe dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems that intracellular reserves of PHB also play an important role in the freezing survival of bacteria, which is in agreement with the observations of other authors. Pavez et al identified PHA accumulation in the bacterium Sphingopyxis chilensis (isolated from an oligotrophic aquatic environment where the temperature oscillates around 0°C) as the most important feature protecting cells from freezing conditions [ 13 ]. Moreover, PHA-producing bacteria were isolated from Antarctic freshwater [ 14 ] and Antarctic soil [ 15 ] confirming PHA accumulation as an efficient adaptation strategy for avoiding damage produced by intracellular ice crystals, oxygen-reactive species, and severe dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…The PHB biosynthetic genes of the bacterium are located within an adaptive genomic island and were probably acquired by horizontal gene transfer, which suggests the importance of PHA accumulation in adaptation to stress conditions, such as those found in the extreme Antarctic environment [ 12 ]. Further, Pavez et al reported that PHAs exert a protective effect against freezing in Sphingopyxis chilensis [ 13 ]. Numerous PHA-producing bacterial strains have also been isolated from Antarctic freshwater [ 14 ] and Antarctic soil [ 15 ], which indicates that PHA accumulation is a common metabolic strategy adopted by many bacteria to cope with cold environments.…”
Section: Introductionmentioning
confidence: 99%
“…These polyesters are produced when bacterial growth is limited by depletion of nitrogen or phosphorous, or when an excess of carbon source is available [9] . For example, Sphingopyxis chilensis survived during carbon starvation or frozen conditions by consuming the accumulated PHAs [10] . PHAs are composed of 3-hydroxy fatty acid monomers, which form linear, head-to-tail polyester molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In Sphingopyxis chilensis, for instance, PHA has been reported to exert a protective effect against carbon starvation and frozen conditions (Pavez, Castillo, Gonz alez, & Martínez, 2009), and an increased abundance of PHA synthesis-related enzymes, including PhaP, was observed at low temperature in Sphingopyxis alaskensis (Ting et al, 2010). Among other cold-adapted microorganisms that may utilize PHA for their growth is the sea-ice bacterium Colwellia psychrerythraea that possesses a significant capacity to produce and degrade fatty acids, providing substrates for mclPHAs biosynthesis (Methé et al, 2005).…”
Section: Resistance To Coldmentioning
confidence: 98%